The Impact of David GadgetIn’s Credibility, Attractiveness, and Product Match-up to Customer Purchase Intention with the Mediator of Customer Attitude in the Case of Tokopedia - Angela Saphira Giovani; Velina Gunawan (iBuss Management, 2022)
The prevalence of e-commerce has started the new era of online shopping and drove up the business even further which also drove up the industry competition. Tokopedia currently leads the online market with one of their marketing strategies by collaborating with endorsers. Therefore, this research aims to analyze the impact of David GadgetIn’ characteristics towards customer purchase intention with the mediator of customer attitude to analyze the effectiveness of the digital marketing strategy of Tokopedia. This research is done through a simple random sampling, with online questionnaires as a data gathering method. The data are gathered from 123 respondents from Indonesia and analyzed using PLS-SEM.  The findings show that credibility is fully mediated by customer attitude to significantly affect purchase intention, while attractiveness is not mediated by customer attitude, and directly influences purchase intention. Lastly, product match-up is neither mediated by customer attitude nor affect purchase intention.Keywords: Endorser, Credibility, Attractiveness, Product match-up, Customer attitude, Purchase intention, David GadgetIn, Tokopedia